Complicated type B aortic dissection causing ischemia in the celiac and inferior mesenteric artery distribution despite patent superior mesenteric artery bypass. (August 2015) - Afifi, Rana O; Zhu, Youwei; Leake, Samuel S; Kott, Amy; Azizzadeh, Ali; Estrera, Anthony L; Safi, Hazim J; Charlton-Ouw, Kristofer M
Mortality rates associated with acute type B aortic dissection (ABAD) complicated by malperfusion remains significant. Optimal management of patients with ABAD is still debatable. We present a case report of a 50-year-old man who was admitted due to ABAD. He was treated medically with his pain resolved and he was discharged on oral antihypertensive medications. One month after initial diagnosis, he was readmitted with abdominal pain, nausea, vomiting, and diarrhea. On imaging, an extension of the aortic dissection into the visceral arteries with occlusion of the celiac and superior mesenteric arteries (SMA) was noted. He underwent thoracic endovascular aortic repair (TEVAR) and bypass grafting to the SMA. Despite the intervention, the patient developed large bowel, liver, and gastric ischemia and underwent bowel resection. He died from multi-organ failure. In selected cases of uncomplicated ABAD, TEVAR should be considered and when TEVAR fails and visceral malperfusion develops, an aggressive revascularization of multiple visceral arteries should be attempted.